Discrepancies between leg-to-leg bioelectrical Impedance analysis and computerized tomography in abdominal visceral fat measurement - Hsueh-Kuan Lu (Nature Portfolio, 2017)
Abstract The aim of this study was to evaluate leg-to-leg bioelectrical impedance analysis (LBIA) using a four-contact electrode system for measuring abdominal visceral fat area (VFA). The present study recruited 381 (240 male and 141 female) Chinese participants to compare VFA measurements estimated by a standing LBIA system (VFALBIA) with computerized tomography (CT) scanned at the L4-L5 vertebrae (VFACT). The total mean body mass index (BMI) was 24.7 ± 4.2 kg/m2. Correlation analysis, regression analysis, Bland-Altman plot, and paired sample t-tests were used to analyze the accuracy of the VFALBIA. For the total subjects, the regression line was VFALBIA = 0.698 VFACT + 29.521, (correlation coefficient (r) = 0.789, standard estimate of error (SEE) = 24.470 cm2, p < 0.001), Lin’s correlation coefficient (CCC) was 0.785; and the limit of agreement (LOA; mean difference ±2 standard deviation) ranged from −43.950 to 67.951 cm2, LOA% (given as a percentage of mean value measured by the CT) was 48.2%. VFALBIA and VFACT showed significant difference (p < 0.001). Collectively, the current study indicates that LBIA has limited potential to accurately estimate visceral fat in a clinical setting.